Energetyka odnawialna w świetle wskaźników zrównoważonego rozwoju systemów energetycznych - Rusak, Helena (Renewable Energy Sources and the Indicators of Sustainable Development of Energy Systems, 2009)
The aim of this article is the analysis of indicators of the sustainable development of energy systems. It divides indicators into two groups. The first contains independent indicators from the quantity of the energy produced in renewable sources. The second one assembles indicators which value is dependent on the quantity of the renewable energy produced in the system. It results from the analysis that all coefficients which concern the technology of producing the energy and primary consumptions of energy are related to the quantity of produced renewable energy in the system.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 83, s. 31-39